2020
DOI: 10.1007/s11033-020-05421-7
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mononuclear cell microRNA profiles in syphilitic patients with serofast status

Abstract: Background Syphilis is a chronic sexually transmitted disease caused by infection with Treponema pallidum, which can invade various system organs, leading to clinical manifestations such as neurosyphilis, ocular syphilis, and cardiovascular syphilis and seriously endangering human health. Serofast status is a

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“… 37 In addition, known and novel predicted (np)-miRNAs in PBMCs in syphilitic patients with SF were identified and verified, such as miR-338-5p, np-miR-163, np-miR-128, np-miR-244, and np-miR-5. 23 It is evident that the exosome-derived miRNAs from serum and cerebrospinal fluid in neurosyphilis and the miRNAs from PBMCs in SF show distinct expression patterns from the exosome-derived miRNAs in plasma from SF. It is challenging to identify common DEmiRNAs across these groups, possibly due to differences in subject selection and individual variation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 37 In addition, known and novel predicted (np)-miRNAs in PBMCs in syphilitic patients with SF were identified and verified, such as miR-338-5p, np-miR-163, np-miR-128, np-miR-244, and np-miR-5. 23 It is evident that the exosome-derived miRNAs from serum and cerebrospinal fluid in neurosyphilis and the miRNAs from PBMCs in SF show distinct expression patterns from the exosome-derived miRNAs in plasma from SF. It is challenging to identify common DEmiRNAs across these groups, possibly due to differences in subject selection and individual variation.…”
Section: Discussionmentioning
confidence: 98%
“…19–22 Regarding T. pallidum infection, the miRNA profiles in peripheral blood mononuclear cells (PBMCs) of patients with syphilis were investigated. 23–25 Exosomes were isolated from plasma and cerebrospinal fluid, and DEmiRNAs were associated with neurosyphilis. 26 In our previous studies, 27 we found that exosome-derived miR-146a-5p from T. pallidum -stimulated macrophages targets JAM-C , reducing endothelial cells permeability and monocyte transendothelial migration.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Another challenge in the treatment is serofast. The cause of the serofast is still unclear and retreatment to serofast patients can not significantly improve the cure rates ( 71 , 72 ). Prediction of the serofast occurrence is also difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of serofast is still unclear. Possible explanations of the lack of serological response to antisyphilitic therapy include that the patients have undiagnosed neurosyphilis and fail to respond to routine therapy; patients have comorbid HIV, malignancies, or immune diseases; and patients are re-infected by having sex with others ( 71 , 72 ). Prediction of the serofast occurrence is still difficult, and retreatment to serofast patients can not significantly improve the cure rates ( 73 , 74 ).…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Furthermore, miRNA expression differed in peripheral blood mononuclear cells (PBMCs) at various phases of T. pallidum infection [ 32 ]. As a result, the microRNAs in PBMCs might singly or jointly be potential diagnostic biomarkers at different stages of syphilis [ 31 35 ]. MiR-195-5p, miR-101-3p, and miR-223-3p alone or in combination can specifically distinguish syphilis patients from non-syphilis patients [ 32 , 33 ]; miR-101-3p can be used as a diagnostic biomarker for patients with primary syphilis [ 31 ].…”
Section: Diagnosismentioning
confidence: 99%